PREPARATION AND SELECTION OF KAZAKH STUDENTS IN THE COMMUNIST UNIVERSITY OF WORKERS OF THE EAST (Journal of history-rus, 2024)
The Communist University of the Toilers of the East (KUTV) is an educational institution organised by the Comintern (Communist International) from 1921 to 1938. The activities of this educational institution were carried out in two directions. The first was the spread of socialist ideology and the development of the socialist movement of the peoples of the East outside the territory of Soviet power, and the second was the training of personnel from representatives of the local population of the East for service by the direction of the ideology. Party personnel for the countries of Central Asia, the Far East, and the North Caucasus were trained here. Graduates of this University became the basis of the new proletarian intelligentsia in their countries. In the article presented to you, the object of research was the development and change of KUTV requirements for admitting students. Accordingly, one can see the formation of a system of communist (party) education in Kazakhstan and the USSR. In the 1920s, the complex social situation after the Civil War and the onset of mass enrollment in higher education reduced the quality of students at universities. The work of the admission committee of the Communist University with such a large number of students is described in detail here.